Higher Education General Information Survey (HEGIS), 1972-1973: Salaries, Tenure, and Fringe Benefits of Full-Time Faculty ([Verlag nicht ermittelbar], 1999)
The Higher Education General Information Survey (HEGIS) series was designed to provide comprehensive information on various aspects of postsecondary education in the United States and its territories (American Samoa, Guam, Puerto Rico, the Virgin Islands, and the Marshall Islands) and Department of Defense schools outside the United States. Data are available for both public and private two-year and four-year institutions. The HEGIS Salaries component for 1972-1973 sought data from institutions of higher education. Key data elements, presented for up to four record types for each institution (corresponding to length of contract and sex), include number of faculty, salaries, and academic rank.